Dissemination of values and culture through the e-folklore - Abd Rahim, Normaliza; Nik Muhammad Affendi, Nik Rafidah; Awang Pawi, Awang Azman (Sakarya Universitesi, 2017)
This study focuses on the values and culture in the e-folklore. The objectives of the study were to identify and discuss the values in the song lyric ‘The Stork and the Mouse Deer’. The song was taken from phone application in the compilation of the ‘Kingfisher stories’ copyrighted by Dewan Bahasa and Pustaka. The e-folklore was rewritten from the Malay folklore stories. The results of the study showed that the stork has more values as compared to the mouse deer. The stork has good, honest, trust, believe, helpful and concern towards others by giving advices while the mouse deer has good values as in being clever and brilliant. It can be seen that the good values will be disseminated through the e-folklore in order to ensure the readers understand the true meaning of the each values and adapt the values in their everyday lives. This study has used the Malay Methodology theory by Hashim Awang (1994) which states that in all aspects of life there are ways in dealing with life, trust and culture among the society and related to humanity. It is hoped that further studies will focus on the values of efolklore between human and animals.